Ontario [1962] - Department of Mines and Technical Surveys (Producer)
Map of Ontario showing cities and towns, provincial parks, First Nations reserves, bodies of water, and other major landmarks. Legend in the lower left corner denotes population density, roads, railways, and capital cities. Scales is 1:2,000,000, Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .